2017
DOI: 10.1111/1365-2435.13022
|View full text |Cite
|
Sign up to set email alerts
|

Paternal‐effects in a terrestrial ectotherm are temperature dependent but no evidence for adaptive effects

Abstract: Global rising of average temperatures and increase in extreme climatic events may largely impact animal survival and reproduction. Yet, how variation in temperature may affect male fertility, in particular ejaculate traits, and whether this can in turn affect offspring fitness, is seldom addressed. Paternal effects may be of key importance as they could impact the rate and direction of evolutionary change in response to climate change. We tested the effects of temperature experienced by males on sperm traits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Within ecologically relevant boundaries, spermatozoa of some species can be remarkably tolerant to changes in temperature in terms of their absolute capacity to activate and fertilise oocytes. Nevertheless, there is evidence that changes in temperature experienced by males (or their ejaculates) prior to conception can have important implications for offspring fitness (Gasparini et al 2018, Kekäläinen et al 2018. Recent work suggests that epigenetic alterations to the germline may drive such effects.…”
Section: Thermal Environmentmentioning
confidence: 99%
“…Within ecologically relevant boundaries, spermatozoa of some species can be remarkably tolerant to changes in temperature in terms of their absolute capacity to activate and fertilise oocytes. Nevertheless, there is evidence that changes in temperature experienced by males (or their ejaculates) prior to conception can have important implications for offspring fitness (Gasparini et al 2018, Kekäläinen et al 2018. Recent work suggests that epigenetic alterations to the germline may drive such effects.…”
Section: Thermal Environmentmentioning
confidence: 99%
“…In particular, sex peptides (SP) are harmful proteins that alter female fecundity and decrease their sexual receptivity, with important carry-over effects on their immunity, life span and fitness (Gioti et al, 2012;Perry et al, 2013;Wigby & Chapman, 2005). Studies conducted in other insects show that temperature can influence male fertility via damage to the testes and/ or sperm (Gasparini, Lu, Dingemanse Niels, & Tuni, 2017;Jørgensen, Sørensen, & Bundgaard, 2006;Lacoume, Bressac, & Chevrier, 2007;Nguyen, Bressac, & Chevrier, 2013;Rohmer, David, Moreteau, & Joly, 2004). Similarly, two studies in other Drosophilid species found that temperature affected sperm motility and fertility and ultimately caused partial sterility (Jørgensen et al, 2006;Rohmer et al, 2004).…”
Section: What Mechanisms Underlie Temperature Modulation Of Male Hamentioning
confidence: 99%
“…For example, a recent study in the Mediterranean field cricket (Grillus bimaculatus) showed that 4ºC temperature differences (within the natural range of variation of the study population in the wild) significantly affected sperm production and quality. Males had higher sperm production and quality when they were exposed to hotter temperatures throughout development, but the opposite was true if they were exposed to hotter temperatures as adults (Gasparini et al, 2017). In addition, temperature also impacted on offspring fitness via effects on male sperm (i.e.…”
Section: Specific Pathways For Temperature Effects On Sexual Selmentioning
confidence: 99%
“…In most systems, we ignore whether cross-generational effects driven by paternal environment are driven by epigenetic mechanisms or mediated by other factors (e.g. direct or female-moderated paternal effects arising from variation in the nonsperm fraction of the ejaculate (Garcia-Gonzalez & Simmons, 2007;Gasparini et al, 2018)).…”
Section: Processes Involved In Effects Of Temperature On Sexual Sementioning
confidence: 99%